Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T17:40:05+01:00
2t - (3t + 1) = 6
2t-3t-1=6
-t=6+1
-t=7
t=-7

-(4 + x) = 2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10

3(y+6) - y = 2(y+9)
3y+18-y=2y+18
2y-2y=18-18
0=0
y∈R

(x-7) - 2(3x+5) = 3
x-7-6x-10=3
-5x=3+17
-5x=20 /:(-5)
x=-4

5 3 5
2010-02-01T17:41:05+01:00
2t - (3t + 1) = 6
2t - 3t - 1 = 6
-t = 6+1
-t=7
t = 7

________________

-(4 + x) = 2(3-x)
-4 -x = 6 - 2x
- x + 2x = 6+4
x= 10

_____________________

3(y+6) - y = 2(y=9)
3y + 18 -y = 2y + 18
2y - 2y = 18 - 18
0=0

_____________________

(x-7) - 2(3x+5) = 3
x - 7 - 6x - 10 = 3
-5x = 3 + 17
-5x = 20
x = -4
2 2 2
2010-02-01T17:41:18+01:00
1)
2t - (3t + 1) = 6
2t -3t -1 = 6
-t = 6 + 1
-t = 7
t = -7

2)
-(4 + x) = 2(3-x)
-4 -x = 6 -2x
-x +2x = 6 +4
x = 10

3)
3(y+6) - y = 2(y=9)
3y + 18 -y = 2y + 18
2y -2y = 18 -18
0 = 0 (tożsamość)

4)
(x-7) - 2(3x+5) = 3
x -7 -6x -10 = 3
-5x = 3 +17
-5x = 20
x = 20 : (-5)
x = -4

2 4 2